The roles of H1, the histone core and DNA length in the unfolding of nucleosomes at low ionic strength. - Burch, J B (1980)
Calf thymus nucleosomes exhibit two different and independent hydrodynamic responses to diminishing salt concentration. One change is gradual over the range 40 to 0.2 mM Na+ and is accompanied by decreases in contact-site cross-linking efficiency. The other change is abrupt, being centered between 1 and 2 mM Na+. We found only one abrupt change in sedimentation rate for particles ranging in DNA content fom 144 to 230 base pairs. This response to decreasing ionic strength is similar for particles of both 169 and 230 base pairs. Core particles (144 base pairs) exhibit a somewhat diminished response. The abrupt change is blocked by formaldehyde or dimethylsuberimidate cross-linking. The blockage by dimethylsuberimidate demonstrates that the abrupt conformational change requires the participation of the core histones. H1 completely blocks the abrupt but not the gradual conformational change. Thus H1 uncouples the different responses to low ionic strength and exerts an important constraint on the conformational states available to the nucleosome core.